Hunting Resource Management by Population Size Control by Remote Sensing Using an Unmanned Aerial Vehicle - S. Ivanova and A. Prosekov (Nature Environment and Pollution Technology, 2024)
The study was carried out on the territory of the Kemerovo region-Kuzbass (Western Siberia, Russia). The purpose of the study was to obtain information on the species diversity and population of big-game animals. The monitoring was carried out on the forest territories of the region’s administrative districts. In the course of remote sensing using an unmanned aerial vehicle, the presence of all types of animals under consideration, except for the bear, was recorded. The deviation of the population number determined using the traditional method of digital technologies varied up to 50%. It was established that environmental measures organized and carried out by the regional administration and hunting farms improved the situation and stabilized the population of the main group of game animals. It was found that when using a sufficiently high sensitivity of the thermal imager (the used thermal imager had a very high sensitivity class ≤ 60 mK at 300 K), long-haired animals, which are characterized by a lower intensity of thermal radiation (for example, wolves) are identified and recognized in the images. The larger the animal and the worse the thermal insulation layer (wool or feathers), the easier it is to identify it in infrared images and the lower the sensitivity requirements of thermal imagers. The ability to recognize and record smaller animals and birds requires additional research on existing technologies. Our research has confirmed the validity of digital remote monitoring methods for managing the wildlife of hunting farms and nature conservation areas of the Siberian Taiga territories.